Multidrug Resistant Pseudomonas Mycotic Pseudoaneurysm following Cardiac Transplant Bridged by Ventricular Assistant Device - C. Aye; M. Williams; R. Horvath (Case Reports in Infectious Diseases)
Mycotic pseudoaneurysm of aorta following cardiac surgery is rare but is highly fatal if it is unrecognized and untreated. Here, we report a case of a 45-year-old male patient who presented with rapidly progressive multiple pseudoaneurysms of the ascending aorta infected with multidrug resistant (MDR) Pseudomonas aeruginosa at 5 weeks after cardiac transplantation, on a background of prior bridging therapy with left ventricular assistant device (LVAD). The patient was successfully treated with the newer cephalosporin, Ceftolozane/Tazobactam, in combination with surgery. This is the first reported case of mycotic pseudoaneurysm infected with MDR Pseudomonas. This case also highlights the importance of high vigilance and timely multimodality treatment in the diagnosis and management of mycotic pseudoaneurysm following cardiac transplant, especially in patients who had LVAD.